Evaluation of Joint Forest Management Programme in India - Chandresh Guleria; Manoj Kumar Vaidya (International Journal of Economic Plants)
The Joint Forest Management (JFM) program is a co-management system for protection, regeneration and development of degraded forests which acted as a bridge between the State and the people dependent on forests. Majority of India’s rural population living in the forest rich regions is poor and their poverty issue can be solved by sustainable management and proper utilization of forest resources. Forest management in India evolved with a stress on commercial plantation after independence, thus relegating the development and conservation needs of forest communities. The JFM in West Bengal was the first plan which was successful in rejuvenating degraded forests during 1972 near Arabari in Midnapore district. JFM involves sharing of responsibilities and rights of local communities and forest department as primary stakeholders in forest management system. There were more than 1,18,213 JFMCs  by 2011, covering 22.94 million ha forests of the country. About 14.5 million families including 4.6 million scheduled tribe families and scheduled caste families are involved in JFM (ICFRE, 2011). Although an overall increase is recorded in the number of JFMCs but the area covered under forests has decreased. There has been downward correction in number of JFMCs and forest area covered in the states of Andhra Pradesh, Himachal Pradesh, Mizoram and Punjab because many registered JFMCs were found non-functional. JFM flourished and reached its peak in the first half of the past decade leading up to 2006-2007 in terms of imitation and impact, after which it got stagnated. Still it is functioning in several areas and has potential to be improved.